2013
DOI: 10.5430/jst.v3n5p30
|View full text |Cite
|
Sign up to set email alerts
|

The natural product NI-07 demonstrates effective anti-cancer properties against numerous cancer cell types

Abstract: Background: With the exception of a few anticancer agents, most chemotherapeutics currently used have varying effects on cancer cells and devastating effects on normal cells. Previously, we showed the natural product compound NI-07 was effective against breast cancer cells. Here, we investigated its effectiveness in vitro on six different cancer types. Additionally, NI-07 was tested in vivo by injecting human melanoma cells WM-266-4 into BALB/c mice and treating with NI-07, cisplatin or untreated. Methods: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, when these natural compounds enter the cytosol, they may act as either competitive inhibitors, binding to the Akt active site and thereby blocking ATP binding and its consequent activation [42] or behave as allosteric inhibitors by binding to the PH domain of the protein, thereby altering the Akt tertiary structure, which affects its function and makes Akt binding to other proteins impossible [42]. While the exact mechanism(s) of action of CGA-CA's inhibition of Akt activation may not be known, our previous work [18,20,21], taken together with this study, suggests that phytochemicals affect multiple molecular targets in the cells to bring about their biological effects. One of these mechanisms involves the downregulation of Akt activation.…”
Section: Study Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, when these natural compounds enter the cytosol, they may act as either competitive inhibitors, binding to the Akt active site and thereby blocking ATP binding and its consequent activation [42] or behave as allosteric inhibitors by binding to the PH domain of the protein, thereby altering the Akt tertiary structure, which affects its function and makes Akt binding to other proteins impossible [42]. While the exact mechanism(s) of action of CGA-CA's inhibition of Akt activation may not be known, our previous work [18,20,21], taken together with this study, suggests that phytochemicals affect multiple molecular targets in the cells to bring about their biological effects. One of these mechanisms involves the downregulation of Akt activation.…”
Section: Study Limitationsmentioning
confidence: 96%
“…Combinations of different phytochemicals for treatments of cancer cells have been shown to produce a stronger biological impact than the individual components [ 17 , 18 , 19 ]. In our prior studies [ 18 , 20 , 21 ], it was shown that plant extracts within a mixture killed cancer cells with little or no cytotoxicity to normal cells. Thus, the idea was not to specifically target metastatic cancer cells but to exploit the co-evolutionary relationship of humans with natural products to “shower the cells” with phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…While other methods have shown simultaneous promise and challenges, the use of plant-derived natural compounds has been proven to hold the much-sought-after Ehrlich’s “poison arrow”. This is because of their unmatched effectiveness in their cytotoxic effects against breast cancer cells and other types of neoplastic diseases, their bioavailability, and safety to normal cells as well as their capability to prevent cancer relapse [ 4 , 5 , 7 , 8 , 9 , 10 , 42 , 43 , 44 ].…”
Section: The Need For Safer/more Effective Alternative Breast Cancer ...mentioning
confidence: 99%
“…Moreover, research into natural compounds as an alternative method in cancer treatment has received overwhelming interest owing to their relative safety and ability to affect multiple molecular targets in cancer cells. Phytochemical agents have been reported to show effectiveness against different types of cancer including various types of breast cancer through varied mechanistic processes such as the induction of apoptosis, the inhibition of DNA replication, the inhibition of telomerase, the dysregulation of mitotic cell division, angiogenic and metastatic process inhibition, and the induction of differentiation in cancer cells [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation